The prediction of cervical cancer screening beliefs based on big five personality traits - Farzaneh Rashidi Fakari; Farnaz Mohammadzadeh; Fahimeh Rashidi Fakari; Marzieh Saei Ghare Naz; Giti Ozgoli (Wiley, 2020)
Abstract Aim The present study was designed with the aim to predict Pap smear screening beliefs based on Big Five personality traits. Design The present cross‐sectional study was conducted with 235 women over 18 years of age in Tehran (Iran) in 2018. Methods The data collection tools included the demographic information questionnaire, Pap Smear Belief Questionnaire (PSBQ) and the 10‐item measure of the Big Five personality traits. Results People with Agreeableness personality trait were more faced with risks and Barriers and factors associated with Pap smear screening beliefs; and those with Conscientiousness personality trait were more faced with risks and Barriers. Results of the present study can help to understand how the personality affects decision‐making and interactions. Therefore, consequences of counselling about screening beliefs and behavioural changes can be improved by personality‐based education.